POLYSPLENIA SYNDROME : A CASE ASSOCIATED WITH ABERRANT RIGHT SUBCLAVIAN ARTERY WITH COMMON ORIGIN OF CAROTID ARTERIES AND LEFT SIDED INFERIOR VENA CAVA WITH BOTH AZYGOUS AND HEMIAZYGOUS CONTINUATION (Journal of Forensic Medicine & Toxicology, 2012)
This paper presents a 17 years old female with recurrent chest infections with idiopathic etiology presenting as polysplenia syndrome with cardiovascular manifestations. In addition to multiple spleens, the thoracic findings included a ‘left’ sided inferior vena cava with both azygous and hemiazygous continuation. The cardiovascular findings revealed an anomalous origin of right subclavian artery along with common origin for carotid arteries.
Keywords: Polysplenia; Inferior Vena Cava; Subclavian; Azygous; Hemiazygous